2015
DOI: 10.1111/1365-2478.12206
|View full text |Cite
|
Sign up to set email alerts
|

Influence of water pressure dynamics and fluid flow on the streaming‐potential response for unsaturated conditions

Abstract: International audienceA B S T R A C T Streaming-potentials are produced by electrokinetic effects in relation to fluid flow and are used for geophysical prospecting. The aim of this study is to model streaming potential measurements for unsaturated conditions using an empirical approach. A conceptual model is applied to streaming potential measurements obtained from two drainage experiments in sand. The streaming potential data presented here show a non-monotonous behaviour with increasing water saturation, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 81 publications
(182 reference statements)
0
30
0
Order By: Relevance
“…A non-monotonous behaviour is supported by the observations of Allègre et al (2010) and also by the observations of Revil et al (2007) and Revil and Cerepi (2004) as detailed in Allègre et al (2011). Recently Allègre et al (2015) showed that the interface between water and air should also be taken into account, since this interface is negatively charged, as the interface between the rock matrix and the water. Moreover during a drainage the amount of this interface does not decrease with decreasing water saturation, but first increases before decreasing, leading to a non-monotonic behaviour of the resulting SPC (Allègre et al, 2015).…”
Section: Effect Of Water Contentmentioning
confidence: 60%
See 1 more Smart Citation
“…A non-monotonous behaviour is supported by the observations of Allègre et al (2010) and also by the observations of Revil et al (2007) and Revil and Cerepi (2004) as detailed in Allègre et al (2011). Recently Allègre et al (2015) showed that the interface between water and air should also be taken into account, since this interface is negatively charged, as the interface between the rock matrix and the water. Moreover during a drainage the amount of this interface does not decrease with decreasing water saturation, but first increases before decreasing, leading to a non-monotonic behaviour of the resulting SPC (Allègre et al, 2015).…”
Section: Effect Of Water Contentmentioning
confidence: 60%
“…Recently Allègre et al (2015) showed that the interface between water and air should also be taken into account, since this interface is negatively charged, as the interface between the rock matrix and the water. Moreover during a drainage the amount of this interface does not decrease with decreasing water saturation, but first increases before decreasing, leading to a non-monotonic behaviour of the resulting SPC (Allègre et al, 2015). The Table 1 summarises the ratios C s0 (S w )/C sat proposed by different authors.…”
Section: Effect Of Water Contentmentioning
confidence: 99%
“…In eq. (9), we use the following relation, which was experimentally derived from laboratory measurements of the streaming potential coefficient in partially saturated sands and displays a non-monotonic dependence with water saturation (Allègre et al 2010(Allègre et al , 2012(Allègre et al , 2014(Allègre et al , 2015Fiorentino et al 2017):…”
Section: Effective Model Parametersmentioning
confidence: 99%
“…Allegre et al . () studied the streaming potential under unsaturated conditions, although a large number of studies on the electrokinetics of saturated samples have been carried out. The results show that the SPC depends on the dynamics of the driving pressure and the fluid flow for unsaturated conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This means that it could not explain the relationship between the SPC and the permeability in detail for a specific type of porous samples in a small range of permeability. Allegre et al (2015) studied the streaming potential under unsaturated conditions, although a large number of studies on the electrokinetics of saturated samples have been carried out. The results show that the SPC depends on the dynamics of the driving pressure and the fluid flow for unsaturated conditions.…”
Section: Introductionmentioning
confidence: 99%